Next-Generation MicroRNA Expression Profiling Technology Methods and Protocols - Fan, Jian-Bing.; Fan, Jian-Bing. (Methods in Molecular Biology,, 2012)
The rapid pace of microRNA (miRNA) research continues to drive the advances of techniques for miRNA expression profiling, and innovative technologies that are more sensitive, specific, quantitative, and that are compatible with a wide range of biospecimens have been developed during the past few years.  In Next-Generation MicroRNA Expression Profiling Technology: Methods and Protocols, expert researchers in the field contribute detailed examinations of the most current approaches being used today.  This volume includes comprehensive coverage of methodologies that have been developed for miRNA profiling, as well as next-gen sequencing technology, miRNA databases, and specialized applications, such as cancer studies and miRNA-based non-invasive biomarker development.  Written in the highly successful Methods in Molecular Biology™ series format, chapters feature introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls.   Authoritative and cutting-edge, Next-Generation MicroRNA Expression Profiling Technology: Methods and Protocols provides an ideal guide for novices and experts alike who are seeking to utilize these powerful technologies.